2018
DOI: 10.1016/j.buildenv.2018.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Indoor climate experience, migration, and thermal comfort expectation in buildings

Abstract: Advances in heating, ventilation and air conditioning (HVAC) technologies have dramatically improved the indoor thermal environment, but attention should be paid on how this would affect building occupants' thermal comfort perception. In this paper, we studied the mutually dependent relationship between indoor climate experience and occupants' comfort expectation. An intriguing experiment was conducted in China where wintertime indoor thermal environments in northern cities (with district heating) are much war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(34 citation statements)
references
References 32 publications
2
31
0
1
Order By: Relevance
“…al. found that occupants quickly increase their thermal comfort expectations and rarely compromise once raised [38]. Occupants becoming accustomed to, or even demanding, tighter temperature tolerances might explain why tight temperature ranges do not necessarily improve thermal comfort.…”
Section: Discussionmentioning
confidence: 99%
“…al. found that occupants quickly increase their thermal comfort expectations and rarely compromise once raised [38]. Occupants becoming accustomed to, or even demanding, tighter temperature tolerances might explain why tight temperature ranges do not necessarily improve thermal comfort.…”
Section: Discussionmentioning
confidence: 99%
“…However, exploring regional differences in adaptive comfort revealed a potential nudge of the intercept term of the model for naturally ventilated buildings. It stands to reason that, along with climatic drivers and physiological adaptation, there are cultural influences shaping thermal perception of building occupants around the world (Auliciems, 1981;Yao et al, 2009;Schweiker & Wagner, 2015;Luo et al, 2018). The steeper gradient for the Asian subset in Figure 5 suggests occupants of buildings located in Asia are more thermally adaptive than what we saw in the original ASHRAE adaptive comfort standard.…”
Section: Naturally Ventilated Buildingsmentioning
confidence: 85%
“…The overwhelming majority of our time is spent indoors, so it is conceivable that the temperatures we are exposed to inside the built environment exert the more powerful effect on our comfort expectations. Luo et al (2018) showed that indoor exposure can largely shape occupants' expectations of their thermal environment. In their analysis of Database II, reported better predictive capacity of thermal sensation using only indoor air temperature compared to the fully-elaborated heat-balance model (PMV-PPD) requiring six input parameters.…”
Section: Nudging Adaptive Comfort Theorymentioning
confidence: 99%
“…In this regard, it is worth stressing that the adaptation capacity of the occupants' thermal comfort usually has asymmetric trajectories [45]. Users more used to the use of HVAC systems will have therefore more difficulties to increase the limit values of the operative temperature than those not using such systems [45]. For this reason, this study analyzed various tolerance ranges in the adaptive thermal comfort model used in setpoint temperatures.…”
Section: Introductionmentioning
confidence: 99%